Sanksi Adat (Singer) terhadap Kasus Perceraian pada Masyarakat Adat Dayak di Desa Sigi Kalimantan Tengah - Sri Kayun; Gelar Sumbogo Peni (Belom Bahadat, 2021)
This article explores and explains the customary sanctions (singer) of the divorce case of the adat law community in Sigi Village, Central Kalimantan. Problems that occur in society need to be appropriately resolved by prioritizing a sense of justice and a sense of peace by considering the legal provisions that apply in society. Divorce cases that occur are resolved by customary law as an option for the community, especially those who experience problems directly for both parties. The problems discussed in this article are related to the factors that cause divorce and the customary sanctions applied to the parties that cause divorce. The method used is through a qualitative approach, which seeks to understand and describe in-depth matters relating to the phenomenon of research or research, which intends to understand what is experienced by the research subject by describing it in the form of words and language. This particular context is natural and makes use of various scientific methods. The conclusion from the results of this individual research is that the factors that cause divorce in Sigi Village, Central Kalimantan are the existence of an affair or the presence of a third party in the household and sanctions in the form of the singer or customary fines, which refer to the previous customary marriage agreement letter, besides that the customary fine is imposed. Against the party causing the divorce.